The Effect of Work Environment and Work Discipline on Employee Performance Through Individual Characteristics as Intervening Variables at the Regional Office of the Directorate General of Customs and Excise, East Java I - Renaldi, Hagus (Yayasan Gema Bina Nusantara, 2023)
This study aims to see the effect of the work environment and work discipline on employee performance through individual characteristics as intervening variables. This research is an observational study. This study used a cross-sectional method. The sample in this study consisted of 135 employees. This study uses a census sampling technique. Data analysis used path model analysis (path analysis) with the help of the AMOS program version 23. The test results showed that there was no relationship between work environment and individual characteristics, which was positive but not significant. There is a relationship between work discipline and individual characteristics that is positive but not significant. There is a positive and significant relationship between work environment and performance. There is a positive and significant relationship between work discipline and performance. There is a positive and significant relationship between individual characteristics influencing performance